PENGARUH FRAMING DEBAT PRESIDEN TERHADAP KEPUTUSAN MEMILIH MAHASISWA PADA PEMILIHAN UMUM TAHUN 2024. STUDI KORELASIONAL PADA MAHASISWA PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN UNIVERSITAS SULTAN AGENG TIRTAYASA - Fadia Hadifatuzzahra; Ikman Nur Rahman (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This correlational study examines the influence of presidential debate framing on first-time university students’ voting decisions in the 2024 General Election. The population of this study focuses on students of Civic Education (Pancasila and Civic Education) at Sultan Ageng Tirtayasa University, a group assumed to possess high sensitivity to political narratives. The study involved 90 respondents from the 2022–2024 cohorts selected through purposive sampling. The sample criteria included students who had watched at least one session of the presidential debates and were not affiliated with any political party during the campaign period. Data were collected through an online Likert-scale questionnaire administered via Google Forms and analyzed using SPSS version 27. The results of the Pearson Product Moment correlation test indicate a significant positive relationship (r = 0.450; p = 0.001) with a moderate level of correlation. Further multiple regression analysis reveals that the Actor Interaction indicator within the framing dimension is the most dominant predictor (β = 0.282). Thus, these findings confirm that presidential debate framing significantly influences students’ electoral decisions, particularly through the interactional and dynamic dimensions among the candidates as presented in the debates. Keywords: Framing, Presidential Debate, Voting Decision